The Effect Of Company Size, Profitability, Leverage On Company Value (Case Study Of Technology Sector Companies Listed on the Indonesian Stock Exchange 2020-2022) - Handayani, Siti Ririn Dian; Yusnita, Rita Tri; Oktaviani, Nita Fauziah (Universitas Dehasen Bengkulu, 2025)
This research aims to determine the influence of company size, profitability and leverage on company value in technology sector companies listed on the Indonesian stock exchange in 2020-2022. Simultaneous testing shows that the influence of company size which is proxied by the natural logarithm, profitability which is proxied by ROA, and leverage which is proxied by DAR has an effect on company value which is proxied by price book value. Partially, using the test, it can be seen that the influence of company size, which is proxied by the natural logarithm, has a significant effect on company value, which is proxied by the price book volume. However, the influence of profitability as proxied by ROA and the influence of leverage as proxied by DAR do not have a significant effect on company value as proxied by price book value.